The Importance of Scrabble Game: An Experimental Analysis of the Eighth Graders' Vocabulary Mastery at SMP Eka Wijaya Cibinong - Masela, Agie (JET (Journal of English Teaching), 2017)
This research aimed to investigate whether Scrabble game has a significant effect on the eighth graders’ vocabulary mastery. This research was carried out by using experimental research method with one group pretest-posttest design. The eighth graders of class VIII-A were taught vocabularies using Scrabble game. The quantitative data, collected using tests, were analyzed by using the independent and paired sample t-test on SPSS version 19 program. The findings on this research showed the mean scores of pre-test and post-test, which were, 52.40 points and 45.64 respectively; the gain was -6.76 points and the result of hypothesis test, it was found that t count (1.569) was less than t table (2.06). The findings indicated that H0 was accepted. The conclusion of this research was Scrabble had no significant effect on the eighth graders’ vocabulary mastery.